Role of the C-Terminal Binding Protein PXDLS Motif Binding Cleft in Protein Interactions and Transcriptional Repression - Quinlan, Kate G. R. (American Society for Microbiology, 2006)
C-terminal binding proteins (CtBPs) are multifunctional proteins that can mediate gene repression. CtBPs contain a cleft that binds Pro-X-Asp-Leu-Ser (PXDLS) motifs. PXDLS motifs occur in numerous transcription factors and in effectors of gene repression, such as certain histone deacetylases. CtBPs have been depicted as bridging proteins that self-associate and link PXDLS-containing transcription factors to PXDLS-containing chromatin-modifying enzymes. CtBPs also recruit effectors that do not contain recognizable PXDLS motifs. We have investigated the importance of the PXDLS binding cleft to CtBP's interactions with various partner proteins and to its ability to repress transcription. We used CtBP cleft mutant and cleft-filled fusion derivatives to distinguish between partner proteins that bind in the cleft and elsewhere on the CtBP surface. Functional assays demonstrate that CtBP mutants that carry defective clefts retain repression activity when fused to heterologous DNA-binding domains. This result suggests that the cleft is not essential for recruiting effectors. In contrast, when tested in the absence of a fused DNA-binding domain, disruption of the cleft abrogates repression activity. These results demonstrate that the PXDLS binding cleft is functionally important but suggest that it is primarily required for localization of the CtBP complex to promoter-bound transcription factors.